Antiphospholipid IgM antibody response in acute and chronic Mycobacterium tuberculosis mouse infection model. (1st October 2013) - Goodridge, Amador; Zhang, Tianyi; Miyata, Toshiko; Lu, Sangwei; Riley, Lee W.
Abstract Background and Aims The clinical management of tuberculosis (TB) could be greatly improved by an affordable biomarker test to monitor treatment response. Here, we examined changes in immunoglobulin M (IgM) antibody response to lipids as a potential biomarker for monitoring TB treatment in an experimental mouse model. Methods We performed enzyme‐linked immunosorbent assay to investigate changes in IgM antibody response against cardiolipin (CL), phosphatidylcholine (PTC), phosphatidylethanolamine (PE), phosphatidylinositol (PI) and sphingolipid (SL) in BALB/c mice that were treated after being infected with Mycobacterium tuberculosis for 4 weeks (acute infection) and 20 weeks (chronic infection). Cytokine levels [interleukin (IL)‐5, IL‐10, interferon‐gamma (IFN‐γ), monocyte chemoattractant protein‐1 (MCP‐1)] in lung and spleen homogenates as well as in blood were also compared. Results In both acutely and chronically infected mice, lungs were sterilised of M. tuberculosis infection after 8 weeks of treatment. The IgM response to CL, PTC, PE, PI and SL were consistently elevated throughout the course of infection in chronically infected mice compared with acutely infected mice. In acutely infected mice, the IgM antibody response against CL significantly decreased after 8 weeks of treatment, but not against other lipids. In chronically infected mice, the IgM response showed no significant changes against any of the lipids after 8 weeks of treatment. Of the cytokines examined, only MCP‐1 levels in lungs decreased significantly after treatment. Conclusion These findings demonstrate that antilipid IgM antibody can remain elevated in chronically infected mice, but with treatment, only anti‐CL IgM antibody levels decreased together with M. tuberculosis bacterial burden in acutely infected mice. Treatment did not affect antilipid IgM levels in chronically infected mice.